Educational Inequalities and Public Policies in Latin America and Europe during the XXI Century (Foro de Educacion, 2021)
The analysis of educational inequalities is a relevant issue due to its interrelation with other inequalities (social, geographical and labor), with migratory processes, with the opportunities for intergenerational social mobility and because they condition the differential strategies, resources and capacities to face the associated risks to them. Addressing educational inequalities from comparative studies is also relevant, since it allows considering the public policies implemented before them, with special emphasis on educational policies. The monograph that is presented is, in itself, a current expression of the diversity of comparative studies in education that can be carried out at different levels, both between countries and within countries; in order to better understand how global and regional phenomena, supranational entities and international agendas impact locally on educational systems, educational policies and educational trajectories.